Bearing capacity of the facade system under temperature effect - Tusnina, Valentina (IOP conference series. Materials Science and Engineering, 2020)
Hinged facade systems are the external enclosing structures of buildings. These systems are subject to a range of loads, including temperature effects. Temperature effects significantly affect the structural bearing capacity. This article presents the results of experimental and theoretical studies of the bearing capacity of a hinged facade system, taking into account the influence of temperature load on the example of a design with gear assemblies of flexible fastening of facing panels. An assessment of the stress-strain state of nodal structural elements is given. A comparative analysis of the strength and deformability of suspended facade systems with flexible and rigid joints of structural elements is given. On the basis of experimental studies, it was found that to ensure free movement during temperature influences in riveted joints, it is necessary to place the rivet "head" in the oval hole and press the rod into the round hole. Assessment of the stress-strain state of the connecting elements in flexible nodes showed that stresses from the temperature load arising in the supporting brackets are very small and amount to ∼ 1.5% of the maximum allowable stresses. This allows us to conclude that these stresses can be ignored.